A Igreja Católica nos "Anos de Chumbo": resistência e deslegitimação do Estado autoritário brasileiro 1968-1974 - Cardonha, José (2011)
Investigates the reaction of the progressive Catholics against the military dictatorship in Brazil mainly based on official and formerly classified documents currently available at Arquivo Público do Estado de São Paulo - APESP. This work demonstrates that the progressive sectors of the Catholic Church resisted against the authoritarian state and worked for its moral deligitimation in several ways: politically, with the condemnation of the systematic violation of the Human Rights; ideologically, with the exposition of the totalitarian tendency of the National Security Doctrine; and economically, with critics to a model that stimulated income concentration and social marginalization